Strengthening of cultural identity in fourth grade children through dance workshops - Casas Vásquez, Gladys Katheryn (2024)
The loss of cultural identity in children is a problem that afflicts today. That is why this study aimed to design dance workshops to improve cultural identity in fourth grade children, which is based on theories of sociocultural learning and multiple intelligences. A descriptive-propositional design was used, under the non-experimental quantitative approach, the sample was 20 students, selected with an intentional non-probabilistic sampling, resulting in more than 50% of the respondents being at a low and very high level. low in cultural identity. Therefore, dance workshops are proposed as a pertinent solution. As a result, after applying the academic proposal, it is expected to achieve the improvement of the cultural identity of all the students participating in the workshops and that through folk dance they know and value their culture. The impact of this research is scientific, due to its novelty, giving rise to different future investigations; educational by promoting the development of skills in educational and social agents because it contributes to society in general.